Two wrongs do not make a right: a critical assessment of Zimbabwe's demobilization and reintegration programmes, 1980-2000 - Mazarire, Gerald C.; Rupiya, Martin R. (Centre for Defence Studies, University of Zimbabwe, 2016)
This article examines the two attempts by Zimbabwe at demobilization since 1980, which have both failed dismally so far. The plight of the 'Class of 83', who require basic support in the form of being afforded opportunities for skills training in order to fit them for a new role in society, is still to be addressed. Not only must they be equipped with useful skills but employment opportunities must also be created for them. Secondly, while this is taking place, enough resources in the form of basic accommodation and minimum survival and welfare must be made available to the core affected group.